Controlo de Manipulador Paralelo para Montagem de Rolhas Capsuladas - Pedro Manuel Morais Martins Santos (2019)
This master thesis aims to develop an automated two-piece assembly system in order to produce capsulated stoppers, using a cork stopper and a capsule. Both elements can have different shapes and materials. The parallel manipulator must be able to identify the capsules through a vision system and place them in the cork. In addition, the system must be able to inspect the final product in order to approve its quality.